Radial growth of Pinus massoniana is influenced by temperature, precipitation, and site conditions on the regional scale: A meta-analysis based on tree-ring width index - Xin Huang (Elsevier, 2021)
The effects of temperature and precipitation on tree growth of given species may vary across its distribution range. To determine how temperature and precipitation influence tree radial growth, we conducted a dendrochronology-based meta-analysis using a network of 113 tree-ring width chronologies of Pinus massoniana trees from the geographical range of the species in southern China. Our results revealed that the difference in the sensitivity of P. massoniana growth to temperature and precipitation was not observed in the entire tree species distribution and each sub-region (all P > 0.05), indicating that there are similarities with respect to the effects of temperature and precipitation on P. massoniana growth among different regions. January–March temperature (T1–3), June–August temperature (T6–8), and July–September precipitation (P7–9) were the key climate signals influencing P. massoniana growth. T1–3 and P7–9 generally enhanced tree growth, whereas T6–8 lead to a decrease in tree growth. Sites with significant negative correlations between tree-ring width index (RWI) and T1–3 showed a northward shift (P < 0.05). The mean latitude of sites with negative correlations was 29.98 ± 0.77°N, whereas the mean latitudes of sites with a non-significant or positive correlation were 27.27 ± 0.28° and 27.34 ± 0.46°N, respectively. The three correlation classes (i.e., positive, negative and non-significant) between T6–8 and RWI showed no significant shifts in longitude, latitude, and elevation (P > 0.05), indicating that high summer temperatures are widespread climate stressors for this species. The growth-climate relationship was determined by combinations of both temperature and precipitation condition of the sampling sites. Temperature seasonality, temperature annual range, and mean temperature of driest quarter of the sampling sites were major contributors to this relationship. These findings have crucial implications for predicting tree growth, introducing the selection of appropriate provenance for afforestation, as well as for climate reconstruction at the regional scale.